Karakteristik Fisik, Kimia dan Mineral Tanah Di Lokasi Kampus IAIN- Ambon Kecamatan Sirimau Kota Ambon - Anggi Asafita Lattupeirissa; Marcus Luhukay; Robby G Risamasu (Fakultas Pertanian, Universitas Pattimura, 2022)
The aims of this study was to identify morphological characteristics, clay mineral composition and soil similarity index between two soil profiles at the IAIN campus. The results showed that soil color characteristics of soil layers of both soils are different. Both soil profiles have deep solums with loam to sandy loam texture distribution. The increasing of clay content in the B horizon of both soil profiles is still weak as indicated by the present of a Bw (kambik) horizon. Soil structure is a subangular blocky with fine to coarse sizes and weak to strong structural development. Soil consistency is slightly sticky to sticky. Cation exchange capacity is very low as indicated by low Ca dan Na, medium to high Mg and high Na soil exchangeable cations. The dominant clay mineral in both soil profiles is kaolonit, which is formed by unwell-consolidated weathering materials mixed with weathering-resistant quartz. The silt/clay ratio and CEC values shows similarity between layers between both profiles, however, the Ca/Mg ratio shows dissimilarity. The soil type in both soil profiles is district Kambisol (Typic distrudepts) categorized as a developed soil